2002
DOI: 10.1046/j.0007-1323.2002.02058.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk of femoral hernia after inguinal herniorrhaphy

Abstract: This study of 34 849 groin hernia repairs demonstrated a 15-fold greater incidence of femoral hernia after inguinal herniorrhaphy compared with the spontaneous incidence. These femoral recurrences occurred earlier than inguinal recurrences, suggesting that they were possibly femoral hernias overlooked at the primary operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
37
0
7

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(46 citation statements)
references
References 10 publications
2
37
0
7
Order By: Relevance
“…A study from the Danish Hernia Database demonstrated a 15-fold greater incidence of femoral hernias after inguinal hernia repair compared with spontaneous incidence [30]. These femoral recurrences occurred earlier than inguinal recurrences, suggesting that they were possibly femoral hernias overlooked at the primary operation [30]. All femoral recurrences occurred after a previous open anterior operation [31].…”
Section: Primary Unilateral Inguinal Hernia In Womenmentioning
confidence: 99%
See 1 more Smart Citation
“…A study from the Danish Hernia Database demonstrated a 15-fold greater incidence of femoral hernias after inguinal hernia repair compared with spontaneous incidence [30]. These femoral recurrences occurred earlier than inguinal recurrences, suggesting that they were possibly femoral hernias overlooked at the primary operation [30]. All femoral recurrences occurred after a previous open anterior operation [31].…”
Section: Primary Unilateral Inguinal Hernia In Womenmentioning
confidence: 99%
“…In a systematic review and meta-analysis of observational studies concerning patientrelated risk factors for recurrence, female sex was found to be a significant risk factor for recurrence after inguinal hernia surgery [29]. A study from the Danish Hernia Database demonstrated a 15-fold greater incidence of femoral hernias after inguinal hernia repair compared with spontaneous incidence [30]. These femoral recurrences occurred earlier than inguinal recurrences, suggesting that they were possibly femoral hernias overlooked at the primary operation [30].…”
Section: Primary Unilateral Inguinal Hernia In Womenmentioning
confidence: 99%
“…Femoral hernias were also more common in patients with recurrent hernia, occurring at a 15-fold higher rate in patients who had undergone inguinal hernia surgery than in those who had not undergone any prior surgery [27]. In the present retrospective study we found twice as many femoral hernias among patients with hernia recurrence (11.1% versus 5.1%).…”
Section: Discussionmentioning
confidence: 79%
“…In men we observed ascendance of the femoral hernias on the left side. Mikkelsen et al (28) create a term of a high risk group for patients with femoral hernias. The group includes elderly patients previously operated due to groin hernia.…”
Section: Discussionmentioning
confidence: 99%